Novel Viral Sequences in a Patient with Cryptogenic Liver Cirrhosis Revealed by Serum Virome Sequencing - Zhang, Xiaoan; Fan, Ida X.; Xu, Yanjuan; Rule, Jody; Tse, Long Ping Victor; Pourkarim, Mahmoud Reza; Lee, William M.; Di Bisceglie, Adrian M.; Fan, Xiaofeng (Viruses, 2025)
Clinical studies indicate the etiology of liver disease to be unknown in 5% to 30% of patients. A long-standing hypothesis is the existence of unknown viruses beyond hepatitis A through E virus. We conducted serum virome sequencing in nine patients with cryptogenic liver disease and identified eight contigs that could not be annotated. One was determined to be a contaminant, while two of seven contigs from an individual (Patient 3) were validated by reverse transcription and polymerase chain reaction (RT-PCR) and Sanger sequencing. The possibility of contamination was completely excluded through PCR, with templates extracted using different methods from samples taken at different time points. One of the contigs, Seq260, was characterized as negative-sense single-stranded DNA via enzymatic digestion and genome walking. Digital-droplet PCR revealed the copy number of Seq260 to be low: 343 copies/mL. Seq260-based nested PCR screening was negative in 200 blood donors and 225 patients with liver disease with/without known etiologies. None of the seven contigs from Patient 3 was mapped onto 118,713 viral metagenomic data. Conclusively, we discovered seven unknown contigs from a patient with cryptogenic liver cirrhosis. These sequences are likely from a novel human virus with a negative-sense, linear single-stranded DNA genome.